A second independent Tyr168Cys mutation in the tissue inhibitor of metalloproteinases-3 (TIMP3) in Sorsby's fundus dystrophy. Issue 3 (March 1996) - Felbor, U; Stöhr, H; Amann, T; Schönherr, U; Apfelstedt-Sylla, E; Weber, B H
Abstract : Sorsby's fundus dystrophy (SFD) is a rare autosomal dominant macular disorder with age of onset usually in the fourth decade. It is characterised by loss of central vision owing to subretinal neovascularisation and disciform macular degeneration. In an effort to identify the SFD gene, the disease locus was first mapped to chromosome 22q13-qter by genetic linkage analysis, the same chromosomal region as the gene encoding the tissue inhibitor of metalloproteinases-3 (TIMP3). Subsequently, two separate mutations in TIMP3 were found in affected members of two unrelated SFD pedigrees (Tyr168Cys and Ser181Cys). More recently, two additional SFD related mutations, Ser156Cys and Gly167Cys, have provided further confirmation that heterozygous mutations in TIMP3 are causally responsible for the SFD phenotype. We now report the occurrence of the Tyr168Cys mutation in an SFD patient of Austrian descent and show that this mutation found earlier in an American SFD family arose independently. The new findings add to an emerging pattern of SFD mutations which all seem to affect the C-terminal region of the mature TIMP3 protein. In addition, all known mutations cause a change of an amino acid to a cysteine residue. This suggests a critical role for the additional C-terminal free thiol group in SFD pathogenesis.